What drives India's outward FDI? - Peter Nunnenkamp; Maximiliano Sosa Andrés; Krishna Chaitanya Vadlamannati; Andreas Waldkirch (Kiel Institute for the World Economy (IfW), 2012)
We empirically assess the determinants of India's FDI outflows across a large sample of host countries in the 1996-2009 period. Based on gravity model specifications, we employ Poisson pseudo maximum likelihood (PPML) estimators. Major findings include: India's outward FDI is hardly affected by motives to access raw materials or superior technologies. Market-related factors appear to have dominated the location choices of Indian direct investors. A larger Indian diaspora in the host countries attracts more FDI. Finally, it seems that Indian direct investors are relatively resilient to weak institutions and economic instability in the host countries. However, we do not find robust evidence that India provides an alternative source of FDI for countries that traditional investors tend to avoid.
Keywords: F21; 330; FDI outflows; gravity model; PPML; India